(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The primary goal of this study is to investigate the impact of big classrooms on student success throughout the world. The study seeks to answer three questions: What influence do big classrooms have on EFL students’ achievement? What effect does class size have on the tactics utilized by instructors? How do pupils who study in large courses vary from those who study in small classes?